Income diversification and the rural nonfarm economy - Paudel, Susan; Filipski, Mateusz J.; Minten, Bart (International Food Policy Research Institute, 2024)
The rapid transformation of the rural sector between 2011 and 2021 has been well-documented in relation to farming and included profound changes in crops grown, farming practices, markets, and value chains. This transformation has been described in this volume, as well as in Belton and Filipski (2019), Filipski et al. (2020), Boughton et al. (2018), and World Bank (2017). However, this period also witnessed a diversification of activities away from agriculture, with incomes shifting away from reliance on subsistence farming and agriculture in general. The contributions of wage work and rural nonfarm businesses are growing in importance as the rural sector moves beyond an agrarian model in which primary agricultural production is the dominant source of wealth. Though the general equilibrium analysis from Chapter 2 shows that agriculture remains a major driver of economic activity, a micro-level analysis finds that activities either downstream in the food value chain or outside of the food system entirely are now responsible for large shares of rural incomes.